FCM marker importance for MRD assessment in T-cell acute lymphoblastic leukemia: An AIEOP-BFM-ALL-FLOW study group report - Kowarsch, Florian; Maurer-Granofszky, Margarita; Weijler, Lisa; Wödlinger, Matthias; Reiter, Michael; Schumich, Angela; Feuerstein, Tamar; Sala, Simona; Nováková, Michaela; Faggin, Giovanni; Gaipa, Giuseppe; Hrusak, Ondrej; et al. (Cytometry. Part A, 2024)
T-lineage acute lymphoblastic leukemia (T-ALL) accounts for about 15% of pediatric and about 25% of adult ALL cases. Minimal/measurable residual disease (MRD) assessed by flow cytometry (FCM) is an important prognostic indicator for risk stratification. In order to assess the MRD a limited number of antibodies directed against the most discriminative antigens must be selected. We propose a pipeline for evaluating the influence of different markers for cell population classification in FCM data. We use linear support vector machine, fitted to each sample individually to avoid issues with patient and laboratory variations. The best separating hyperplane direction as well as the influence of omitting specific markers is considered. Ninety-one bone marrow samples of 43 pediatric T-ALL patients from five reference laboratories were analyzed by FCM regarding marker importance for blast cell identification using combinations of eight different markers. For all laboratories, CD48 and CD99 were among the top three markers with strongest contribution to the optimal hyperplane, measured by median separating hyperplane coefficient size for all samples per center and time point (diagnosis, Day 15, Day 33). Based on the available limited set tested (CD3, CD4, CD5, CD7, CD8, CD45, CD48, CD99), our findings prove that CD48 and CD99 are useful markers for MRD monitoring in T-ALL. The proposed pipeline can be applied for evaluation of other marker combinations in the future.
Keywords: dospělí; Neoplasm, Residual; akutní lymfatická leukemie; dítě; průtoková cytometrie; Adult; lidé; feature importance; Flow Cytometry; reziduální nádor; flow cytometry; T-lymfocyty; minimal residual disease; lymfoblastická leukemie-lymfom z prekurzorových T-buněk; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Child; CD99; Precursor T-Cell Lymphoblastic Leukemia-Lymphoma; support vector machine; T-Lymphocytes; T-lineage acute lymphoblastic leukemia; CD48; Humans